THE STAGES OF SCIENTIFIC APPROACH IMPLEMENTED BY A STATE VOCATIONAL HIGH SCHOOL ENGLISH TEACHER (RETAIN, 2016)
THE STAGES OF SCIENTIFIC APPROACH IMPLEMENTED BY A STATE VOCATIONAL HIGH SCHOOL ENGLISH TEACHER Ardi Rama English Department, Faculty of Langauge and Art, State University of Surabaya ardam_plok@yahoo.co.id Prof. Dr. Susanto, M.Pd. English Department, Faculty of Langauge and Art, State University of Surabaya susantoniki@gmail.com Abstrak Pendekatan Saintifik digunakan pada kurikulum 2013. Pendekatan ini diterapkan ke dalam semua mata pelajaran, termasuk Bahasa Inggris. Pendekatan ini terdiri dari lima tahap dan satu tahap pilihan, yaitu: tahap mengamati, menanya, mengeksperimen/mengumpulkan informasi, mengasosiasi/mengalanalisa mengkumonukasi dan membuat (pilihan). Penelitian sebelumnya, Wardani (2014) mengadakan analisa tahap-tahap Pendekatan Saintifik pada enam RPP SMP kurikulm 2013, namun belum membahas bagaimana guru penerapan tahap-tahap tersebut di dalam kelas. peneliti memilih guru sebuah SMK Negeri sebagai subyek penelitian. Pertanyaannya: (1) bagaimana Guru Bahasa Inggris menerapkan tahap mengamati di SMK Negeri (2) bagaimana Guru Bahasa Inggris menerapkan tahap menanya di SMK Negeri (3) bagaimana Guru Bahasa Inggris menerapkan tahap mengeksperimen/ mengumpulkan informasi di SMK Negeri (4) bagaimana Guru Bahasa Inggris menerapkan tahap menasosiasi/menganalisa di SMK Negeri (5) bagaimana Guru Bahasa Inggris menerapkan tahap mengkomunisikan di SMK Negeri (6) bagaimana Guru Bahasa Inggris menerapkan tahap membuat (pilihan) di SMK Negeri. Peneliti menggunakan deskriptif kualitatif, dengan instrument observasi dan wawancara. Hasilnya, ditemukan bawa guru Bahasa Inggris menerapkan tiga tahap Pendekatan Saintifik secara tepat (tahap mengamati, mengasosiasi, dan mengkomunikasi), dua tahap secara rata-rata (tahap menanya dan mengeksplorasi) dan tidak merapkan satu tahap (tahap membuat). Kata Kunci: pendekatan saintifik, aktifitas guru. Abstract Scientific Approach becomes the main approach in 2013 Curriculum. This approach is expected to be implemented in every subject, including English. Scientific Approach consists of five stages and one optional stage, namely: observing stage, questioning stage, experimenting/collecting information stage, associating/analyzing stage, communicating stage and creating stage (optional). From previous study of Wardani, (2014) she had only analyzed six Junior High School lesson plan of 2013 Curriculum, not focusing on the implementation of Scientific Approach in the classroom. It was become the initial idea of having a research of the stages of Scientific Approach implemented by a State Vocational High School English Teacher. The research questions are; (1) how the English teacher implements observing stage in State Vocational High School (2) how the English teacher implements questioning stage in State Vocational High School (3) how the English teacher implements experimenting/collecting information stage in State Vocational High School (4) how the English teacher implements associating/analyzing stage in State Vocational High School (5) how the English teacher implements communicating stage in State Vocational High School (6) how the English teacher implements creating stage in State Vocational High School. The research applied descriptive qualitative research. The instruments of this research were observation and in-depth interview. Based on the result, it was found that the English teacher of State Vocational High School implemented three stages of Scientific Approach properly (observing stage, associating stage and communicating stage), two stages averagely (questioning stage and exploring stage) and did not implement one stage (creating stage). Keywords: scientific approach, teacher’s activities.